2013
DOI: 10.1002/jso.23312
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR‐19a expression correlates with worse prognosis of patients with non‐small cell lung cancer

Abstract: High serum miR-19a expression may be an independent poor prognostic factor for survival in NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
68
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 32 publications
5
68
0
2
Order By: Relevance
“…42,[49][50][51][52][53][54][55][56][57] In addition, miR-19 upregulation was observed in various cancers including lung cancer, and correlated with tumor metastasis and/or poor prognosis of cancer patients. [11][12][13][14][15]18 Given that miRNAs primarily function through inhibiting the translation of their mRNA targets, we propose that miR-19 might be a negative regulator for PTEN, which has been reported by other researchers. 10,29,58,59 In addition, miR-19 increased the resistance to apoptosis of mouse B-cell lymphoma, 10,29 and chemoresistance of human breast cancer 58 and gastric cancer 59 through directly repressing PTEN expression.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…42,[49][50][51][52][53][54][55][56][57] In addition, miR-19 upregulation was observed in various cancers including lung cancer, and correlated with tumor metastasis and/or poor prognosis of cancer patients. [11][12][13][14][15]18 Given that miRNAs primarily function through inhibiting the translation of their mRNA targets, we propose that miR-19 might be a negative regulator for PTEN, which has been reported by other researchers. 10,29,58,59 In addition, miR-19 increased the resistance to apoptosis of mouse B-cell lymphoma, 10,29 and chemoresistance of human breast cancer 58 and gastric cancer 59 through directly repressing PTEN expression.…”
Section: Discussionsupporting
confidence: 71%
“…It has been reported that miR-19 was dysregulated in various cancers, and miR-19 upregulation strongly correlated with gain of invasive and metastatic properties and poor prognosis of patients with NSCLC, [11][12][13] gastric cancer, 14 and esophageal squamous cell carcinoma. 15 Moreover, the expression of miR-19 was significantly higher in the lessinvasive breast cancer MCF7 cells than the more-invasive MDAMB-231 cells, and the expression of a positive regulator of tumor angiogenesis and metastasis was negatively regulated by miR-19 in breast cancer cells, 35 suggesting that miR-19 inhibited the metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations